Perancangan IoT Pada Sistem Kontrol Lampu Menggunakan Telegram - Ibnu Ramadhan, Kemal; Reihan Ferdian Utomo, Diva; Rizqy Alfiansyah, Rafif; Izzy Gian Anargia, David; Pramono (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The development of the Internet of Things (IoT) has enabled better integration between electronic devices and internet networks, creating new opportunities for remote control of devices. One example is controlling lights using Telegram as a communication interface. This research aims to design an IoT lighting control system connected to Telegram, allowing users to access and control lights remotely via the Telegram application. The system consists of a sensor to detect light intensity, a microcontroller to process data, and a communication module to send instructions to the lamp via relay. Users can send commands via Telegram to turn lights on, off, or adjust the brightness of lights according to their preferences, as well as program light responses based on environmental conditions. By leveraging a broad IoT infrastructure and communications platforms, such as Telegram, the system provides easy access and flexible control, offering the potential for practical implementation in a variety of contexts, including smart homes, offices, or urban environments.